2008
DOI: 10.1016/j.virol.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the DNA-binding protein (DBP) of the Autographa californica multiple nucleopolyhedrovirus

Abstract: DNA-binding protein (DBP) of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) was expressed as an N-terminal His(6)-tag fusion using a recombinant baculovirus and purified to near homogeneity. Purified DBP formed oligomers that were crosslinked by redox reagents resulting in predominantly protein dimers and tetramers. In gel retardation assays, DBP showed a high affinity for single-stranded oligonucleotides and was able to compete with another baculovirus SSB protein, LEF-3, for binding sites. DBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Viruses with DNA genomes also require SSBs for replication of their genomes, and several have been identified in such diverse eukaryotic virus families as Adenoviridae, Herpesviridae, and Poxviridae. LEF-3 shares properties with these other well-characterized SSBs: it binds ssDNA (15,45); it oligomerizes in solution (33,34); it interacts with the helicase P143 (7,45); it closely associates with the viral DNA polymerase and the potential initiator IE-1 on viral DNA (17); it localizes to the nucleus (1); it can both unwind DNA duplexes and assist in annealing cDNA strands (31).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses with DNA genomes also require SSBs for replication of their genomes, and several have been identified in such diverse eukaryotic virus families as Adenoviridae, Herpesviridae, and Poxviridae. LEF-3 shares properties with these other well-characterized SSBs: it binds ssDNA (15,45); it oligomerizes in solution (33,34); it interacts with the helicase P143 (7,45); it closely associates with the viral DNA polymerase and the potential initiator IE-1 on viral DNA (17); it localizes to the nucleus (1); it can both unwind DNA duplexes and assist in annealing cDNA strands (31).…”
Section: Discussionmentioning
confidence: 99%
“…3). These include two genes encoding proteins involved in the preparation of DNA for transcription; single stranded DNA binding protein (Mikhailov et al. , 1998, 2008) and LEF‐3 (Mikhailov, 2000, 2006), and three genes encoding immediate‐early activators of viral transcription regulatory proteins, IE‐0, IE‐1 and IE‐2 (Kovacs et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA-binding protein (DBP) has also been reported to be a replication factor for BmNPV (Mikhailov et al, 1998). The interactions among these replication-associated proteins have been investigated in several studies and the interactions of LEF1-LEF2 and LEF3-helicase (Evans et al, 1999) and the self-associations of LEF3 , IE1 (Olson et al, 2001;Rodems & Friesen, 1995), IE2 (Imai et al, 2000) and DBP (Mikhailov et al, 2008) have been reported. In addition, some interactions in which replication-associated proteins were …”
Section: Dna Replicationmentioning
confidence: 99%